2013
DOI: 10.1016/j.jacc.2013.01.080
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic Consequences of Gestational Dysglycemia

Abstract: The development of gestational diabetes and even milder forms of dysglycemia during pregnancy represents a maternal phenotype at increased subsequent risk for developing type 2 diabetes mellitus, metabolic syndrome, and, with time, overt cardiovascular disease. A careful and systematic dissection of the hormonal, metabolic, and vascular changes occurring in such women during pregnancy and over the postpartum years provides a unique opportunity to identify conventional and novel conditions and biomarkers whose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 67 publications
0
28
0
Order By: Relevance
“…In this study, we observed a significant association between GDM and CVD among both obese and non-obese women, although the association seemed stronger among obese women compared to non-obese women. Previous studies have shown that altered lipid metabolism, impaired endothelial function, and vascular inflammation may be implicated in the pathogenesis of CVD after GDM (31, 32). Our results indicate that low levels of HDL cholesterol may contribute to the increased risk of CVD in women with prior GDM.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we observed a significant association between GDM and CVD among both obese and non-obese women, although the association seemed stronger among obese women compared to non-obese women. Previous studies have shown that altered lipid metabolism, impaired endothelial function, and vascular inflammation may be implicated in the pathogenesis of CVD after GDM (31, 32). Our results indicate that low levels of HDL cholesterol may contribute to the increased risk of CVD in women with prior GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, among non-Koreans, women with histories of GDM had greater vascular resistance, lower stroke volume, lower cardiac output [83]. Small cross-sectional studies conflict as to whether flow mediated dilation is impaired among women with histories of GDM [84]. Among Italian women, women with GDM had higher carotid intimal medial thickness at approximately 6.5 years postpartum compared to women without histories of GDM [85], even after adjustment for other cardiovascular disease (CVD) risk factors.…”
Section: Postpartum Maternal Outcomesmentioning
confidence: 99%
“…44 Recent data showed that in addition to gestational diabetes mellitus, even mild forms of dysglycemia during pregnancy represent a maternal phenotype of increased subsequent cardiometabolic risk. 45 Our data revealed that the MetS participants underwent a progressive worsening of glucose metabolism from enrollment at gestational age of 11 +0 to 13 +6 weeks, to at term, and to ≈1.6 years postpartum. This finding is consistent with a recent report that β-cell function declines within the first year postpartum.…”
Section: Lei Et Al Prehypertension and Postpartum Metabolic Syndrome 461mentioning
confidence: 63%